Social divisions in discursive approach - case study of 2015 parliamentary elections in Poland - Domagała, Katarzyna; Zieliński, Mateusz (Political Preferences, 2018)
Many political scientists treat Poland as a democracy that confront the challenges from the "tyranny of the majority", since Law and Justice (Prawo i Sprawiedliwość, PiS) party gained parliamentary majority in 2015. It is also considered that using constitutional amendments, institutional arrangements and new legislation PiS has deeply divided Polish society. The aim of the paper is to examine the multidimensional nature of hidden social divisions that strongly reapear in Poland after 2015. In the paper authors analyze their historical aspects, visualize them and try to disclose direct impact that political narration of the winning party has on them. By analyzing PiS stance – presented at the official PiS YouTube channel – in the light of classical Lipset-Rokkan theory of socio-political cleavages we are trying to show that discursive strategies adopting by parties might go against existing deep-rooted social divisions due to historical narration adopted by the party. Key words: Post-Rokkanian analysis, Semantic Network Analysis, cleavages